4(z+7)-(2z-1)=z

Simple and best practice solution for 4(z+7)-(2z-1)=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(z+7)-(2z-1)=z equation:


Simplifying
4(z + 7) + -1(2z + -1) = z

Reorder the terms:
4(7 + z) + -1(2z + -1) = z
(7 * 4 + z * 4) + -1(2z + -1) = z
(28 + 4z) + -1(2z + -1) = z

Reorder the terms:
28 + 4z + -1(-1 + 2z) = z
28 + 4z + (-1 * -1 + 2z * -1) = z
28 + 4z + (1 + -2z) = z

Reorder the terms:
28 + 1 + 4z + -2z = z

Combine like terms: 28 + 1 = 29
29 + 4z + -2z = z

Combine like terms: 4z + -2z = 2z
29 + 2z = z

Solving
29 + 2z = z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
29 + 2z + -1z = z + -1z

Combine like terms: 2z + -1z = 1z
29 + 1z = z + -1z

Combine like terms: z + -1z = 0
29 + 1z = 0

Add '-29' to each side of the equation.
29 + -29 + 1z = 0 + -29

Combine like terms: 29 + -29 = 0
0 + 1z = 0 + -29
1z = 0 + -29

Combine like terms: 0 + -29 = -29
1z = -29

Divide each side by '1'.
z = -29

Simplifying
z = -29

See similar equations:

| 8x-2x(x-9)=2(x-5)+1 | | X=-1-1*-1 | | 2/x-3=26/x | | 4(z+7)-(2x-1)=z | | 4c^2+19c-21=0 | | X=-8-1*-1 | | 16-(4M+8)=5+4M-13 | | (-1)-2*6= | | X=-8-y | | 3/4v=6 | | 6-8-(-12)-14-3*3*2*2= | | 5x+b=192 | | (-4)+(-2)*(-3)= | | 0=0.25x^2-5x+80 | | y=0.25x^2-5x+80 | | (-6)-(-10)= | | 0.8q+q=8(0.6q-2) | | 4x+2y+7+4x+3y= | | f(-1)=2x-3x | | 2x^2+x+1=25 | | 5y+y=90 | | 6-4(2-5x)= | | 8(m+3)=4 | | 11+5x=4x-20 | | log[2](-6-5x)=2 | | 8p^2-4p=o | | 4=2x^2-24x+76 | | x-8=4x+1 | | 2.50+5.75=56 | | log(5x-7)=3 | | (8.2h)/2=36.1 | | 21x^6+42x^2=7x^2 |

Equations solver categories